A contribuição do modelo de gestão CERNE para a sustentabilidade da Incubadora Santos Dumont do Parque Tecnológico Itaipu – Brasil (PTI) - Caus, Gabriel Delallo (2023)
Incubators of technology-based companies play a fundamental role in fostering innovative entrepreneurship in the various regions of the country, from those focused on the local development of a given region with specific performance in a given sector, to larger incubators linked to technological parks and large universities. With these diverse possibilities of purposes, it is fundamental that business incubators are well managed in order to maximize the value for entrepreneurs and guarantee their sustainability. Thus, this research aimed to understand the contribution of the CERNE (Reference Center for Support to New Ventures) management model to the sustainability of the Santos Dumont Incubator (ISD) of the Itaipu Technological Park – Brazil (PTI-BR). To attain the proposed objective, a qualitative approach research was carried out, of descriptive character, being a case study to understand the CERNE management model applied to the Santos Dumont Incubator. The study used records in files, internal documents of the incubator, participant observation and questionnaires with 14 incubated companies, six graduated companies, 11 professionals from the incubator’s management and operations team, and three other incubators of companies also certified at level 4 of CERNE were interviewed. The research results demonstrate that the CERNE management model contributes directly to the generation of successful business and to the incubator’s sustainability, as long as it is well planned, applied and monitored by the management team, aiming to make the operation fluid and not plastered, with the main highlights being the perception of an increase in brand value and the analysis of the learnings on the part of the management team. The research also contributed by detailing the Santos Dumont incubation and acceleration methodology, which can serve as inspiration for other incubators to improve the level of incubated ventures.